2022
DOI: 10.3389/fpsyg.2022.870574
|View full text |Cite
|
Sign up to set email alerts
|

Innovating workplace learning: Training methodology analysis based on content, instructional design, programmed learning, and recommendation framework

Abstract: The quality of sales processes is crucial in automotive and directly related to the firm’s competitive advantage and financial success. Sales training is the most prevalent intervention to guarantee quality and productivity. Extant literature has attempted to measure training effectiveness adequately, and the Context, Input, Process, and Product evaluation (CIPP) model has been a popular approach. This study endeavored to advance current literature and suggest a novel effectiveness framework, Content, Instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…According to Raemy and Barabasch (2022), this focus on dealing with changes also stimulates employee resilience toward further changes and toward their work. Kim (2022) instead proposes to consider learning transferability, or “the ability to apply the knowledge an individual learned in different situations,” as one of the prominent causes of improved performance. Understanding how employees can use and share their new knowledge relies on individual actions, not on how knowledge is imparted initially.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Raemy and Barabasch (2022), this focus on dealing with changes also stimulates employee resilience toward further changes and toward their work. Kim (2022) instead proposes to consider learning transferability, or “the ability to apply the knowledge an individual learned in different situations,” as one of the prominent causes of improved performance. Understanding how employees can use and share their new knowledge relies on individual actions, not on how knowledge is imparted initially.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding how employees can use and share their new knowledge relies on individual actions, not on how knowledge is imparted initially. For this reason, many researchers ground their research on self-determination theory, as it offers a solid explanation for many observed behaviors in all forms of learning, especially education (Kim, 2022; Thomas et al. , 2022; Baber et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the systemic approach to corporate employee training and development has been elaborated on in a number of literary sources, including books, journals, and the Internet [17,[35][36][37]. It should be noted, however, that a rigorous analysis of educational needs is not always carried out in practice.…”
mentioning
confidence: 99%